Survey of ICT and Education in Africa : Central African Republic Country Report - Fall, Babacar (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. The Central African Republic (CAR) faces many challenges to make a greater effort in training, budgeting, and awareness creation concerning the use of ICTs. Introducing ICTs into basic education (especially in secondary education) is increasingly seen by many as a necessity, and the development of teacher skills is necessary to enhance the use of educational technology. The country has only one university and enrolment rates are low for most levels of education. To reverse this situation, the government has made some worthy efforts to promote basic education, such as the building of new schools in the capital and the provinces with assistance from the European Union and the World Bank.